2016
DOI: 10.5545/sv-jme.2015.3305
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Laser Shock Peening on the Surface Integrity of 18 % Ni Maraging Steel

Abstract: Maraging steels represent a special group of ultrahigh strength steels which can be hardened by precipitation of intermetallic compounds at temperatures around 480 °C [1]. These steels have a high content nickel, cobalt, and molybdenum, while the content of carbon, considered an impurity, is kept as low as possible. Commercially available maraging steels can reach yield strengths up to 2400 MPa. In addition to high strength, they are characterized by high resistance to thermal fatigue, high fracture toughness,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The interaction between laser beam size and material affected the propagation nature of the shock waves. Smaller-diameter shock waves probably expand like spheres with a higher attenuation rate than larger-diameter shock waves, which behave like planar fronts [15,16,24,25]. This phenomenon, together with a higher overlapping rate between laser spots, may explain our findings.…”
Section: Residual Stress Measurementsmentioning
confidence: 52%
See 1 more Smart Citation
“…The interaction between laser beam size and material affected the propagation nature of the shock waves. Smaller-diameter shock waves probably expand like spheres with a higher attenuation rate than larger-diameter shock waves, which behave like planar fronts [15,16,24,25]. This phenomenon, together with a higher overlapping rate between laser spots, may explain our findings.…”
Section: Residual Stress Measurementsmentioning
confidence: 52%
“…They found out the LSP generated highly compressive RSs in the component surface layer. Petan et al [16] have also shown that LSP with relatively low pulse energy can generate compressive RSs in maraging steel at a level of 500 MPa. When they increased laser pulse density (PD), the surface roughness increased.…”
Section: Introductionmentioning
confidence: 97%
“…Shot peening increases the high cycle fatigue life and helps to reduce the sensitivity to humid environments [2,18,24,27]. Laser shock peening helps in delaying both crack initiation and propagation [8,9]. Nitriding increases the hardness of the surface and induces compressive residual stress in the surface layer which improves the fatigue life [25,28].…”
Section: Introductionmentioning
confidence: 99%
“…This undesirable effect causes expenses to repair and renovation of parts. Analysis of residual stress is very important [1,2]. Manufacturing process (machining, forming, welding, etc.)…”
Section: Introductionmentioning
confidence: 99%